Answer:
x<4
Move all terms not containing x to the right side of the inequality.
Answer:
-(5 n + 6)
Step-by-step explanation:
Simplify the following:
-4 (n + 1) - (n + 2)
-4 (n + 1) = -4 n - 4:
-4 n - 4 - (n + 2)
-(n + 2) = -n - 2:
-4 - 4 n + -n - 2
Grouping like terms, -4 - 4 n - 2 - n = (-4 n - n) + (-4 - 2):
(-4 n - n) + (-4 - 2)
-4 n - n = -5 n:
-5 n + (-4 - 2)
-4 - 2 = -(4 + 2):
-5 n + -(4 + 2)
4 + 2 = 6:
-5 n - 6
Factor -1 out of -5 n - 6:
Answer: -(5 n + 6)
To find out, graph them, analyze, and check.
Graph them.
You get the graph below.
Check the answers.
It looks like B matches.
So, the answer is B.